Nephroprotective Effects of Caffeine, Vanillin, and Their Combination against Experimental AlCl3-Induced Renal Toxicity in Adult Male Wistar Rats - Olakunle Bamikole Afolabi; Oluwaseun Ruth Olasehinde; Oyindamola Adeniyi Olaoye; Kikelomo Folake Jaiyesimi; Ilobekemen Lisa Ekakitie; Omotade Ibidun Oloyede (Biochemistry Research International)
Aluminum (Al) is known to be a nephrotoxic metal that can cause renal toxicity in both humans and animals. The use of functional foods has been reported to have significance in managing the toxic effects associated with such metals. This study aimed to assess the potential protective effects of caffeine, vanillin, and their combination in mitigating AlCl3-induced renal toxicity in adult male Wistar rats. A total of thirty (30) adult male Wistar rats weighing between 150 and 200 g were randomly divided into five groups, each consisting of six rats (n = 6). Group 1 served as the control, while the remaining treatment groups received a daily oral dose of 100 mg/kg AlCl3 for a duration of 21 days. In addition, groups 3–5 were coadministered 50 mg/kg body weight (bw) of caffeine, vanillin, and a combination (50/50 mg/kg bw) of both substances, respectively. In the results, AlCl3-treated showed a significant (p < 0.05) increase in serum biomarkers such as ALT, ALP, urea, and creatinine, and a significant (p < 0.05) decrease in serum total proteins (TPs). The renal tissue’s antioxidant system, including SOD, CAT, GPx, and GSH, exhibited a significant (p < 0.05) reduction, accompanied by an elevated MDA level. However, the administration of caffeine, vanillin, and their combination resulted in a significant (p < 0.05) decrease in serum ALT, ALP, urea, and creatinine, and a significant (p < 0.05) increase in serum TP. Furthermore, following the treatment, there was a significant (p < 0.05) increase in renal SOD, CAT, GPx, and GSH levels, along with a reduction in the MDA level. In addition, the treatment for 21 days caused a significant (p < 0.05) reversal to the altered histomorphological architecture. These findings suggest that caffeine, vanillin, and their combination could potentially be an effective regimen in managing AlCl3-induced renal toxicity.